D-Dimer, C-Reactive Protein, and Neutrophil-Lymphocyte Ratio As Indicators of the Severity of Covid-19 Patients - ARSANA, I NYOMAN; Susilawati, Ni Wayan; Sudaryati, Ni Luh Gede (JURNAL WIDYA BIOLOGI, 2025)
https://docs.google.com/document/d/1r4A1q90nlA_fpPFh62C_qqP2C8moJIji/edit?usp=sharing&ouid=106483118819211017969&rtpof=true&sd=true